Promoting Physical Activity through Priming the Content of Motivation - St Quinton, Tom (Frontiers in Psychology, 2017)
Nonconscious processes are important in influencing the performance of a number of behaviors, such as physical activity. One way that such processes can be influenced is through priming. Despite this, approaches within health psychology have predominantly focused on reflective processes with a number of psychological theories dedicated to identifying the predictors of intention. In doing so, critical beliefs and thoughts are first identified and then altered within interventions. Such work has shown limited effectiveness, however, with a gap apparent between what one intends to do and what subsequently ensues. Although there have been attempts to bridge this gap, such as theoretical integration, recent efforts include priming implicit processes. The aim of this commentary is to demonstrate the potential effectiveness of priming nonconscious processes and to suggest that the content of motivation should also succumb to priming influences. This brief review suggests that priming one of the most influential conscious processes, that of self-efficacy, could demonstrate particular effectiveness in promoting physical activity. Thus, the main purpose of the article is to suggest that the content of implicit processes as well their more traditional conscious counterparts may provide useful intervention targets. To achieve this, the article will first introduce the role of nonconscious processes and behavioral priming. Following this, the more common reflective processes will be outlined as well as attempts at theoretical integration. Finally, the article will identify studies priming nonconscious processes and will then suggest priming self-efficacy.